Peran Gotong Royong dalam Meningkatkan Solidaritas Sosial dan Meningkatkan Kesadaran Masyarakat terhadap Lingkungan - Maulana Sarfanudin; Anis Zohriyah; Nurmala Sari; Nuriyah Nuriyah; Adi Rizal (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Gotong royong, or mutual cooperation, is a deeply rooted local cultural value in Indonesian society that plays a strategic role in strengthening social cohesion and promoting environmental consciousness. This study aims to explore and analyze the function of gotong royong in fostering social solidarity and raising community awareness of environmental sustainability through various communal activities. These activities include neighborhood cleaning, reforestation efforts, and participatory waste management, all of which require active involvement from community members. Using a qualitative descriptive method, the research was conducted through field observations and in-depth interviews with residents actively engaged in gotong royong practices. The findings reveal that gotong royong serves as a powerful social mechanism that encourages a sense of togetherness, mutual aid, and shared responsibility among community members. These interactions help to solidify social bonds and create a collective spirit that is vital for social resilience. In addition to reinforcing social relationships, the practice of gotong royong significantly contributes to enhancing environmental awareness. Communities become more proactive in maintaining cleanliness, preserving green spaces, planting trees, and managing waste sustainably. The study concludes that gotong royong is not merely a traditional cultural practice, but also an effective and relevant instrument for promoting social and environmental well-being in contemporary society. Its continued integration into community development programs could further strengthen both social solidarity and environmental stewardship, making it a vital component in sustainable development initiatives. Therefore, revitalizing and institutionalizing gotong royong is essential for fostering holistic and inclusive community growth.